Aflibercept in the Treatment of Diabetic Macular Edema: A Review and Consensus Paper. Issue 6 (8th November 2017) - Avitabile, Teresio; Azzolini, Claudio; Bandello, Francesco; Boscia, Francesco; De Falco, Sandro; Fornasari, Diego; Lanzetta, Paolo; Mastropasqua, Leonardo; Midena, Edoardo; Ricci, Federico; Staurenghi, Giovanni; Varano, Monica
Purpose: To reach a consensus, among experts, on the role of aflibercept in diabetic macular edema (DME) through literature review. Methods: Two round tables, involving 12 Italian experts, were organized: in the first one, 6 pharmacologic and clinical questions were selected and analyzed by a systematic literature review, using a population, intervention, control, and outcomes framework; in the second one, the nominal group technique was used to discuss relevant evidence related to each question. The consensus was assessed using the 5-point Delphi score. Results: Agreement on statements was reached on 6/6 questions. The final statements were as follows: 1) High levels of both vascular endothelial growth factor (VEGF) and placental growth factor play an important role in the pathogenesis of DME. 2) The aflibercept pharmacologic profile is notably different from that of other anti-VEGF. 3) Aflibercept significantly improves functional and anatomical outcomes, and rapidly improves best-corrected visual acuity up to its peak; these results remain stable over time. 4) Diabetic macular edema aflibercept treatment requires a 5-monthly injection loading phase. Alternatively, a personalized pro re nata (PRN) regimen based on monthly monitoring and strict retreatment criteria can be used. 5) As an alternative to the bimonthly fixed regimen, in the maintenance phase the treatment schedule may be a PRN regimen with strict retreatment criteria or a treat and extend regimen. 6) No concerns on aflibercept ocular and systemic safety emerged from the literature. Conclusions: Consensus was reached among experts on how to best treat patients with DME with aflibercept.